Kritik Sosial Komunitas DjamurMelalui Mural di Kota Denpasar - Yuliarmini, Ni Made; Kebayantini, Ni Luh Nyoman; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT This study examines social criticism contained in mural works of the Djamur Community in criticizing the phenomena or problems that exist in society. Public sphere according to Jurgen Habermas is a medium that is used to convey a public opinion that requires a handling. Public sphere is able to demonstrate the problems that exist in society in an innovative way. Based on the research that has been done, demonstrating social criticism of problems or phenomena that exist in society has been done innovatively through mural works made in public sphere in Denpasar City. The problems or issues that are often used as the theme in making murals by the Djamur Community are about issues of child violence, environmental issues, and political issues. These cases are deliberately used as themes so that people can see and know these cases and be able to provide relevant solutions or treatments. Keywords: Mural, Public Sphere, Social Criticism